CARRIAGE OF OPPORTUNISTIC MICROORGANISMS AND SURVIVAL OF PATIENTS WITH CHRONIC KIDNEY DISEASE STAGE 5 D - I. M. Shifris (Ukrainian Journal of Nephrology and Dialysis, 2017)
Despite of significant development of dialysis technology, mortality rates of CKD V D stage patients remain unsatisfactorily high. Next to cardiovascular diseases, infections are seems to be as a major causes of morbidity, hospitalization and mortality in this population. Staphylococcus aureus, especially MRSA, infections are a major cause of morbidity and hospitalization in CKD V D stage patients. Preceding MRSA colonization views as a risk factor for subsequent MRSA infections in future.Aim. The aim of this study was to explore the effects of opportunistic pathogens colonization on survival in patients with CKD VD stage.Materials and methods. This prospective cohort, open-label study included 255patients with CKD V D st. (198 HD and 57 PD patients). Patients were randomized into two groups, depending on the MRSA colonization history: first group (n=66) included patients with identified MRSA colonization and the second group (n=189) included patients with colonization of other opportunistic pathogens. The groups were representative according to gender, age, type of kidney affections and renal replacement therapy (RRT) modality. The endpoint was the total number of deaths. All cases, which took place from 01.08.2011 to 01.08.2016 year, were analyzed. The Kaplan-Meier method was perfomed for evaluation of survival. Results. The analysis allowed to state that during analyzed period in total were 75 deaths: in the first group ofpatients - 32 (48.5%), and in the second - 43 (22.8%) cases; %2= 14,38, p = 0,000078; RR – 2,131, 95% ffl: 1,484-3,060.The survival rate of patients was significantly lower in the first group, irrespective of RRT modality. The 3-years cumulative proportion surviving was 53% and 79% in the first (MRSApositive) and second groups, respectively; p< 0,001.Conclusion. This study demonstrated that MRSA asymptomatic colonization has a significant negative effect on survival in the patient population with CKD VD stage